Adult Congenital Heart Disease : Focusing on Intervention - Masuda, Munetaka; Niwa, Koichiro (Springer Singapore : Imprint: Springer, 2017)
This book describes the most popular topics concerning adult congenital heart disease (ACHD), especially focusing on indications and re-intervention procedures for some major ACHDs. Thanks to advances in medical and surgical therapy for congenital heart disease over the last half century, many patients who underwent surgical correction reached adulthood. However, as can be seen from the explosive increase in the number of ACHD patients, postoperative residua and sequelae have also become apparent. The purpose of this book is to highlight complicated problems in connection with ACHD, including its present status, as well as methods for its management including medical and surgical treatment. The content primarily focuses on two areas - general information for cardiologists, and information on re-intervention for interventionists and cardiac surgeons -, setting it apart from the majority of books on congenital heart disease.